Fields of Gold : Financing the Global Land Rush - Fairbairn, Madeleine; Project Muse. (Ithaca [New York] Cornell University Press, 2020)
"Over the last decade, the financial sector has suddenly begun investing in farms; Fields of Gold critically examines the history, ideas, and political struggles surrounding this "financialization of farmland"--
Farmland Investment Comes of Age -- Farmland Values -- The Reluctant Commodity -- Foreign Politics
Description based on print version record.
Keywords: Financialization; Farms -- Foreign ownership; Agriculture -- Finance; Agriculture -- Economic aspects; Agriculture -- Capital investments; SCIENCE -- Earth Sciences -- Geography; Financiarisation; Agriculture -- Aspect economique; Agriculture -- Investissements de capitaux; Agriculture -- Finances; Financialization; Farms -- Foreign ownership; Agriculture -- Economic aspects; Agriculture -- Capital investments; Agriculture -- Finance; Electronic books